Coaching and counseling : a practical guide for managers and team leaders - Minor, Marianne (Crisp Pub. Menlo ParkUS, 1996)
Presents benefits of, and methodology for both coaching and counselling at the workplace; explains how to decide which process is necessary; and suggests ways to give and use feedback effectively.